Pertanggungjawaban pada Tindak Pidana yang Dilakukan Agen Otonom Artificial Intelegence - Sulistio, Faizin; Daffa Salsabilla, Aizahra (Universitas Ekasakti, 2023)
This research tries to find legal solutions related to criminal liability carried out by autonomous agents of artificial intelligence (AI). In this research, problems related to the development of AI-based intelligent robots are increasingly sophisticated and have capabilities similar to humans. This resemblance of AI entities to humans has consequences with actions taken, especially those that can have a negative impact or attack legal interests. Therefore, further regulation is needed related to artificial intelligence accountability as one of the legal entities in criminal law in Indonesia. Then it is also necessary to include AI as a legal subject as a consideration in the future with the hope that AI can be held criminally responsible for their actions that attack legal interests, given the massive development of technology and information that allows everything to be done through AI intermediaries.